Tauopathy in the young autistic brain: novel biomarker and therapeutic target - Grigg, Iris; Ivashko-Pachima, Yanina; Hait, Tom Aharon; Korenková, Vlasta; Touloumi, Olga; Lagoudaki, Roza; Van Dijck, Anke; Marusic, Zlatko; Anicic, Mirna; Vukovic, Jurica; Kooy, R Frank; Grigoriadis, Nikolaos; et al. (Translational psychiatry, 2020)
Given our recent discovery of somatic mutations in autism spectrum disorder (ASD)/intellectual disability (ID) genes in postmortem aged Alzheimer's disease brains correlating with increasing tauopathy, it is important to decipher if tauopathy is underlying brain imaging results of atrophy in ASD/ID children. We concentrated on activity-dependent neuroprotective protein (ADNP), a prevalent autism gene. The unique availability of multiple postmortem brain sections of a 7-year-old male, heterozygous for ADNP de novo mutation c.2244Adup/p.His559Glnfs*3 allowed exploration of tauopathy, reflecting on a general unexplored mechanism. The tested subject exhibited autism, fine motor delays, severe intellectual disability and seizures. The patient died after multiple organ failure following liver transplantation. To compare to other ADNP syndrome mutations, immortalized lymphoblastoid cell lines from three different patients (including ADNP p.Arg216*, p.Lys408Valfs*31, and p.Tyr719* heterozygous dominant mutations) and a control were subjected to RNA-seq. Immunohistochemistry, high-throughput gene expression profiles in numerous postmortem tissues followed. Comparisons to a control brain and to extensive datasets were used. Live cell imaging investigated Tau-microtubule interaction, protecting against tauopathy. Extensive child brain tauopathy paralleled by multiple gene expression changes was discovered. Tauopathy was explained by direct mutation effects on Tau-microtubule interaction and correction by the ADNP active snippet NAP. Significant pathway changes (empirical P value < 0.05) included over 100 genes encompassing neuroactive ligand-receptor and cytokine-cytokine receptor interaction, MAPK and calcium signaling, axon guidance and Wnt signaling pathways. Changes were also seen in steroid biosynthesis genes, suggesting sex differences. Selecting the most affected genes by the ADNP mutations for gene expression analysis, in multiple postmortem tissues, identified Tau (MAPT)-gene-related expression changes compared with extensive normal gene expression (RNA-seq) databases. ADNP showed relatively reduced expression in the ADNP syndrome cerebellum, which was also observed for 25 additional genes (representing >50% of the tested genes), including NLGN1, NLGN2, PAX6, SMARCA4, and SNAP25, converging on nervous system development and tauopathy. NAP provided protection against mutated ADNP disrupted Tau-microtubule association. In conclusion, tauopathy may explain brain-imaging findings in ADNP syndrome children and may provide a new direction for the development of tauopathy protecting drug candidates like NAP in ASD/ID.
Keywords: mozek; mužské pohlaví; Male; Nuclear Proteins; senioři; Female; Humans; DNA Helicases; autistická porucha; jaderné proteiny; Autistic Disorder; tauopatie; Brain; lidé; transkripční faktory; ženské pohlaví; Tauopathies; Nerve Tissue Proteins; Autism Spectrum Disorder; Child; dítě; proteiny nervové tkáně; DNA-helikasy; Transcription Factors; Biomarkers; biologické markery; homeodoménové proteiny; Homeodomain Proteins; poruchy autistického spektra; Aged